Impact of Menstrual Function on Hormonal Response to Repeated Bouts of Intense Exercise - Melin, Anna K.; Ritz, Christian; Faber, Jens; Skouby, Sven; Pingel, Jessica; Sundgot-Borgen, Jorunn; Sjödin, Anders; Tornberg, Åsa B. (Frontiers in Physiology, 2019)
Background Strenous exercise stimulates the hypothalamic-pituitary (HP) axis in order to ensure homeostasis and promote anabolism. Furthermore, exercise stimulates a transient increase in the neurotrophin brain-derived neurotrophic factor (BDNF) suggested to mediate the anxiolytic effects of exercise. Athletes with secondary functional hypothalamic amenorrhea (FHA) have been reported to have lower BDNF, and a blunted HP axis response to exercise as athletes with overtraining syndrome. Aim The aim of the study was to investigate the hormonal and BDNF responses to a two-bout maximal exercise protocol with four hours of recovery in between in FHA and eumenorrheic (EUM) athletes. Methods Eumenorrheic (n = 16) and FHA (n = 14) endurance athletes were recruited from national teams and competitive clubs. Protocols included gynecological examination; body composition (DXA); 7-day assessment of energy availability; blood sampling pre and post the two exercises tests. Results There were no differences between groups in hormonal responses to the first exercise bout. After the second exercise bout IGFBP-3 increased more in FHA compared with EUM athletes (2.1 ± 0.5 vs. 0.6 ± 0.6 μg/L, p = 0.048). There were non-significant trends toward higher increase in IGF-1 (39.3 ± 4.3 vs. 28.0 ± 4.6 μg/L, p = 0.074), BDNF (96.5 ± 22.9 vs. 34.4 ± 23.5 μg/L, p = 0.058), GH to cortisol ratio (0.329 ± 0.010 vs. 0.058 ± 0.010, p = 0.082), and decrease in IGF-1 to IGFBP-3 ratio (−2.04 ± 1.2 vs. 0.92 ± 1.22, p = 0.081) in athletes with FHA compared with EUM athletes. Furthermore, there was a non-significant trend toward a higher increase in prolactin to cortisol ratio in EUM athletes compared with athletes with FHA (0.60 ± 0.15 vs. 0.23 ± 0.15, p = 0.071). No differences in the hormonal or BDNF responses between the two exercise bouts as a result of menstrual function were found. Conclusion No major differences in the hormonal or BDNF responses between the two exercise bouts as a result of menstrual function could be detected.